Sufficiency in social practices: An underestimated potential for the transformation to a circular economy - Suski, Pauline; Palzkill, Alexandra; Speck, Melanie (Frontiers in Sustainability, 2023)
To date, the circular economy has fallen short on its promise to reduce our resource demand and transform our production and consumption system. One key problem is the lack of understanding that highly promising strategies such as refuse, rethink and reduce can be properly addressed using research on sufficiency. This paper argues that a shift in focus is required in research and policy development from consumers who buy and handle circularly designed products to consumption patterns that follow logics of sufficiency and explain how sufficiency-oriented concepts can be incorporated into existing social practices. The authors show that sufficiency is not necessarily as radical and unattractive as is often claimed, making it a suitable yet underrated strategy for sustainability and the transition to an effective circular economy. The case of urban gardening shows that small interventions can have far-reaching effects and transform consumption patterns as logics of availability are contested by newly-developed concepts of ‘enoughness’ and opposition to ‘über-availability’. The authors propose utilizing comprehensive state of the art theories of consumption and human action when developing strategies and policies to make the circular economy sustainable, while being more critical of utilitarian approaches. Using social practice theories that have proven to be beneficial allows human action to be comprehensively analysed by recognizing its embeddedness in social and material frameworks, addressing the meaning, competences and materials of routinised human behaviour and examining indirect effects.